Soil acidification and the liming potential of biochar. (15th January 2023) - Bolan, Nanthi; Sarmah, Ajit K.; Bordoloi, Sanandam; Bolan, Shankar; Padhye, Lokesh P.; Van Zwieten, Lukas; Sooriyakumar, Prasanthi; Khan, Basit Ahmed; Ahmad, Mahtab; Solaiman, Zakaria M.; Rinklebe, Jörg; Wang, Hailong; et al.
Abstract: Soil acidification in managed ecosystems such as agricultural lands principally results from the increased releasing of protons (H + ) from the transformation reactions of carbon (C), nitrogen (N) and sulphur (S) containing compounds. The incorporation of liming materials can neutralize the protons released, hence reducing soil acidity and its adverse impacts to the soil environment, food security, and human health. Biochar derived from organic residues is becoming a source of carbon input to soil and provides multifunctional values. Biochar can be alkaline in nature, with the level of alkalinity dependent upon the feedstock and processing conditions. This review covers the fundamental aspects of soil acidification and of the use of biochar to address constraints related to acidic soil. Biochar is increasingly considered as an effective soil amendment for reducing soil acidity owing to its liming potential, thereby enhancing soil fertility and productivity in acid soils. The ameliorant effect on acid soils is mainly because of the dissolution of carbonates, (hydro)-oxides of the ash fraction of biochar and potential use by microorganisms. Graphical abstract: Image 1 Highlights: In managed ecosystem, soil acidification results mainly from the carbon and nutrient cycling. Acidification is a major soil constraint impacting soil health and heavy metal toxicity. The level of alkalinity in biochar depends on the feedstock and processing conditions. Biochar liming value is derived from carbonates, and hydro-oxides of the ash fraction. Biochar ameliorates acid soils by suppling base cations and reducing aluminium toxicity.